Receptor-Interacting Protein Kinase 3 as a Serological Biomarker in Relation to Disease Severity and Delirium After Acute Pancreatitis: A Prospective Cohort Study - Ye X; Li B; Xu F; Pan D; Wu J (International Journal of General Medicine)
Xiaorong Ye,1 Bingzhen Li,2 Fang Xu,3 Debiao Pan,4 Jing Wu1 1Department of Anorectal Surgery, Lishui Hospital of Wenzhou Medical University, Lishui People’s Hospital, Lishui, Zhejiang Province, People’s Republic of China; 2Department of Gastrointestinal Surgery, Lishui Hospital of Wenzhou Medical University, Lishui People’s Hospital, Lishui, Zhejiang Province, People’s Republic of China; 3Department of Gastroenterology, Lishui Hospital of Wenzhou Medical University, Lishui People’s Hospital, Lishui, Zhejiang Province, People’s Republic of China; 4Department of Hepatobiliary Surgery, Lishui Hospital of Wenzhou Medical University, Lishui People’s Hospital, Lishui, Zhejiang Province, People’s Republic of ChinaCorrespondence: Bingzhen Li, Department of Gastrointestinal Surgery, Lishui Hospital of Wenzhou Medical University, Lishui People’s Hospital, Lishui, Zhejiang Province, People’s Republic of China, Email 18957097838@163.comObjective: Delirium is a common complication of acute pancreatitis. Receptor-interacting protein kinase 3 (RIP3) is an activator of programmed cell necrosis. This study aimed to determine its ability to predict delirium after acute pancreatitis.Methods: In total, 297 patients with acute pancreatitis were prospectively enrolled in this study. Patients were divided into two subgroups (study and validation groups: 197 and 100 cases, respectively). Serum RIP3 levels were measured in all patients and in 100 healthy controls. Acute Physiology and Chronic Health Evaluation (APACHE) II, Ranson, and sequential organ failure assessment (SOFA) scores were used for the severity assessment. In-hospital delirium was observed as an outcome variable. Multifactorial analyses were performed to discern severity correlations and outcome associations.Results: Serum RIP3 levels were significantly higher in the patients than in the controls. Serum RIP3 levels had linear relationships under the restricted cubic spline and were independently correlated with APACHE II, Ranson, and SOFA scores. Serum RIP3 levels were linearly correlated with the likelihood of developing in-hospital delirium and exhibited a strong discrimination efficiency under the receiver operating characteristic curve. Serum RIP3 levels, coupled with APACHE II scores, Ranson scores, and SOFA scores, were the four independent predictors of in-hospital delirium. No interactions were revealed regarding its relevance to sex, age, or body mass index in subgroup analysis. These were integrated to form a model graphically represented by a nomogram that showed effective stability, clinical fit, and predictive ability for in-hospital delirium. The model was verified in the validation group.Conclusion: An incremental trend in serum RIP3 levels was notable after acute pancreatitis. Serum RIP3 levels are independently related to illness severity and occurrence of in-hospital delirium, indicating that serum RIP3 may be a potential biomarker of acute pancreatitis.Keywords: acute pancreatitis, delirium, receptor-interacting protein kinase 3, severity